Alcohol Taxation and Child Maltreatment - Michael McLaughlin (Washington University Journal of Law & Policy, 2019)
Several decades of research have demonstrated that alcohol tax rates are related to a number of alcohol-related harms, including drunk driving, crime, and femicide. However, there is very limited research on the relationship between alcohol taxes and child maltreatment. Two studies examine the effects of beer taxes on physical child abuse, but no research has been done on other types of alcohol taxes or other child maltreatment subtypes. This study performs a comprehensive analysis to assess whether taxes on beer, wine, and spirits are linked to child maltreatment and its various subtypes. A fixed-effects analysis of state-level panel data from 2000 to 2014 suggest that changes in alcohol tax rates predict changes in rates of child abuse and neglect. This relationship is demonstrated for both specific types of alcohol taxes and a weighted-average alcohol index. The findings suggest that alcohol taxes are an additional policy tool that can be used to address child maltreatment.
Keywords: Tax law; Taxation; Child maltreatment; Alcohol; Alcohol taxation; Child abuse and neglect